1997
DOI: 10.1007/s00282-997-0301-3
|View full text |Cite
|
Sign up to set email alerts
|

Repopulation of circulating T, B and NK lymphocytes following bone marrow and blood stem cell transplantation

Abstract: A variety of T, B and natural killer (NK) cell subsets defined by surface markers were analyzed by double immunofluorescence flow cytometry in the peripheral blood of patients following autologous bone marrow transplantation (ABMT, n = 14), autologous peripheral blood stem cell transplantation (PBSCT, n = 10) and allogeneic bone marrow transplantation (allo-BMT, n = 6). Patients following ABMT were divided in 2 groups, those who did not received G-CSF post-transplant (ABMT, n = 6) and those who did (ABMT + G, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…B-cell recovery was also highly variable, whereas NK cells recovered relatively early, consistent with other HCT studies (38)(39)(40). Anti-third-party alloreactivity generally recovered quite early when measured via LDA, and was frequently associated with a 'suppressive' pattern, possibly explaining the frequently weak simultaneous bulk culture alloresponses.…”
Section: Tolerance In Patients With Combined Kidney and Marrow Transpsupporting
confidence: 76%
“…B-cell recovery was also highly variable, whereas NK cells recovered relatively early, consistent with other HCT studies (38)(39)(40). Anti-third-party alloreactivity generally recovered quite early when measured via LDA, and was frequently associated with a 'suppressive' pattern, possibly explaining the frequently weak simultaneous bulk culture alloresponses.…”
Section: Tolerance In Patients With Combined Kidney and Marrow Transpsupporting
confidence: 76%
“…[13][14][15][16][17] This same phenomenon of delayed B and T cell recovery post-ASCT has been reported in patients with metastatic breast cancer. Avigan et al 18 demonstrated abnormalities in T cell phenotype and function in patients followed up to 12 months post-ASCT.…”
Section: Discussionmentioning
confidence: 57%
“…[8][9][10][11][12][13] NK cells comprise 5% to 8% of human peripheral blood lymphocytes and morphologically resemble large granular lymphocytes.…”
mentioning
confidence: 99%